(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Most of the patients with Lumbago sciatica can be managed conservatively in a primary care setting with the expectation of a good outcome. It is one of the most common causes of pain and disability pertinent to lumbar spine. There are many alternative forms of treatment for this condition but the evidence of the efficacy of Indomethacin suppositories is yet to be established from clinical trials. Though several interventions are used in combination with physical therapy but indomethacin suppositories is commonly employed as a first line agent in the management of lumbago sciatica. Objective: To ascertain whether a comparative effect of Indomethacin suppositories with other conventional treatment modalities produce a significant difference in the outcome. Materials and Methods: This experimental clinical study was carried out at the Department of Physical Medicine, Combined Military Hospital (CMH), Dhaka and Department of Physical Medicine and Rehabilitation BSMMU, from 01 September 2015 to 28 February 2016. A total of 153 patients were randomly selected for trial and they were divided by lottery into 3 Groups. Group-“A” received Indomethacin suppositories with physical exercise and patients were 54 in number. ’Group-B’ received NSAIDs (except indomethacin suppositories), SWD /MWD/IFT/TENS and patients were 47. In ’Group-C’ there were 52 patients who received counseling with only physical exercises. Each Group received above-mentioned treatment modalities 5 days in a week for 6 weeks. Results: The results were observed and noted with the help of visual analogue scale (VAS). The highest significant improvement was observed in ’Group-A’ throughout the whole treatment period. The significant difference of improvement was found between groups finally in week 4 (W4) to week 6 (W6). The group received Indomethacin suppositories with physical exercise shows improvement of patients with lumbago sciatica. Conclusion: The use of Indomethacin suppositories with physical therapy and the conventional modalities of treatment comparison help the physician to provide treatment facilities. The result was found better in groups those who received Indomethacin suppositories (Group-A) rather than those Groups who received other conventional treatment modalities. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 28-32